Design of Automatic Mujair Fish Feed Based on Arduino And Telegram - Moch Nando Askitha Videnta; Misbah Misbah; Denny Irawan (Universitas Muhammadiyah Gresik, 2021)
The need for fish consumption in East Java Province in 2012 reached 24.55 kg/capita/year.With a fish consumption rate of 24.55 kg/capita/year, East Java Province must provide 925,139 tons offish to meet the fish consumption of its population within a year. However, considering that theproduction of catch fisheries has decreased due to overfishing. The RPJMN emphasizes the importanceof increasing production from aquaculture, because the potential for land that can be developed forcultivation is still large. This makes land fish farming more intensively developed.Therefore, the final project will be entitled